2012
DOI: 10.5402/2012/291285
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tillage, Irrigation, and Nutrient Levels on Growth and Yield of Sweet Potato in Rice Fallow

Abstract: A field experiment was conducted during the year 2007-2008 and 2008-2009 in Bhubaneswar, India to study the effect of tillage, irrigation and nutrient levels on growth and yield of sweet potato (Ipomoea batatas L.) in rice fallow. The results revealed that the conventional tillage system of sweet potato planting recorded maximum fresh root yield. During the year 2007-2008 and 2008-2009, the fresh root yield in this system was 4.6% and 30.3% higher than the minimum tillage treatment, respectively. Similarly 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 10 publications
6
42
1
1
Order By: Relevance
“…A significant increase in LAI values was observed from 60 DAP to 120 DAP, which can be attributed to the plants still being in the above-ground exponential growth phase. This is somewhat in contrast to the observation of Nedunchezhiyan et al (2012) who observed a decline in LAI values from 95 DAP until harvest. The canopy cover of the sweet potato cultivars were affected by the drought conditions imposed in the three trials, as seen in declining values from control to mild stress and/or severe stress treatments.…”
Section: Trialcontrasting
confidence: 99%
See 3 more Smart Citations
“…A significant increase in LAI values was observed from 60 DAP to 120 DAP, which can be attributed to the plants still being in the above-ground exponential growth phase. This is somewhat in contrast to the observation of Nedunchezhiyan et al (2012) who observed a decline in LAI values from 95 DAP until harvest. The canopy cover of the sweet potato cultivars were affected by the drought conditions imposed in the three trials, as seen in declining values from control to mild stress and/or severe stress treatments.…”
Section: Trialcontrasting
confidence: 99%
“…This in agreement with results obtained by Nedunchezhiyan et al (2012), who observed significant differences in LAI values of sweet potato plantings at different soil water levels. In the present study, the cultivars Isondlo, Purple Sunset, Resisto, W-119 and Zapallo, as well as breeding lines 2005-12-2 and 2006-3-4, showed increasing canopy coverage at 120 DAP when the severe stress treatment is compared to the control treatment ( Table 2).…”
Section: Trialsupporting
confidence: 93%
See 2 more Smart Citations
“…In order to make the maximized profit (Nedunchezhiyan et al, 2007) and acquire higher land equivalent ratio (LER) and yield stability (Wells et al, 2000;Skelton and Barrett, 2005), which was the ultimate aim of intercropping. Maize means shading to a great extent, though excess cloudiness encourage vegetative growth, it causes yield reduction (Nedunchezhiyan et al, 2012), especially main crop (Gliessman, 1985). Mead (1980) claimed that the benefits of multiple cropping are achieved by the simple suitability of growing crops together.…”
Section: Introductionmentioning
confidence: 99%